Therapeutic application of mesenchymal stem cell-derived exosomes in skin wound healing - Sun, Yunhan; Zhang, Shun; Shen, Yukai; Lu, Haoyang; Zhao, Xincan; Wang, Xin; Wang, Yongkai; Wang, Taiping; Liu, Bing; Yao, Lan; Wen, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
Wound healing is a complicated obstacle, especially for chronic wounds. Mesenchymal stem cell-derived exosomes may be a promising cell-free approach for treating skin wound healing. Exosomes can accelerate wound healing by attenuating inflammation, promoting angiogenesis, cell proliferation, extracellular matrix production and remodeling. However, many issues, such as off-target effects and high degradation of exosomes in wound sites need to be addressed before applying into clinical therapy. Therefore, the bioengineering technology has been introduced to modify exosomes with greater stability and specific therapeutic property. To prolong the function time and the local concentration of exosomes in the wound bed, the use of biomaterials to load exosomes emerges as a promising strategy. In this review, we summarize the biogenesis and characteristics of exosomes, the role of exosomes in wound healing, and the therapeutic applications of modified-exosomes in wound healing. The challenges and prospects of exosomes in wound healing are also discussed.